The silent signals: emerging safety concerns in bispecific antibody therapy for multiple myeloma - Xiaoling Zhou; Erdan Luo; Wei Chen; Yi Deng; Bo Wu; Xia Jiang; Kaili Zhang; Fan Lai (Frontiers in Medicine)
BackgroundBispecific antibodies (BsAbs) are widely used for the treatment of multiple myeloma (MM), but their long-term safety still provokes concerns.MethodsAdverse event (AE) data on teclistamab, talquetamab, and elranatamab between 1 August 2022 and 30 September 2024 were retrieved from the Food and Drug Administration’s AE Reporting System (FAERS) database by use of Open Vigil 2.1. AEs were categorized by preferred terms (PTs) and system organ classes (SOCs) as defined by MedDRA. As widely used statistical measures in pharmacovigilance, proportional reporting (PRR) and reporting odds ratios (ROR) were employed to identify potential safety signals.ResultsIn total 2,789,182 reports on AEs were retrieved, including 811 for teclistamab, 446 for talquetamab and 302 for elranatamab. Significant associations with immune system disorders, nervous system disorders, benign, malignant and unspecified (incl cysts and polyps) neoplasms, and hepatobiliary disorders were found for all three BsAbs. Common PTs included cytokine release syndrome (CRS), neurotoxicity, immune effector cell-associated neurotoxicity syn-drome (ICANS), pyrexia, and neutropenia. Meanwhile, signal values varied among the three BsAbs. Notably, new safety signals numbered 14, 4, and 5 were identified for teclistamab, talquetamab, and elranatamab, respectively.ConclusionAdverse event signals were demonstrated to vary among the three BsAbs used in MM. Significant safety signals identified in the FAERS database which were consistent with previously reported clinical trial data. Furthermore, each BsAb exhibited several novel signals. These findings provide decision-makers and healthcare providers with valuable insights into clinical practice.